Rancang Bangun Sistem Pengukur Suhu Tubuh Manusia Jarak Jauh Berbasis Internet Of Things (IOT) - Nuri Afriani, Eka; Djatmiko, Wisnu; Bintoro, Jusuf (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2022)
The purpose of this researcher is to design a remotely-based body temperature gauge system (IOT) at home to improve the security of the spread of Covid-19. The remote body temperature system based on the Internet of Things (IOT) is late finished and has been tested. Tools are compared with digital thermogun namely Infrared Thermometer SK-T008 with an average error rate in percent (error percentage) of 0.438%. LCD 16x2 displays the results of the body temperature value in the Celsius unit and if the body temperature value is more than 37.5 degrees Celsius Then the Buzzer and red LED will be active. If the body temperature is below 35 degrees Celsius, the blue LED will be active.